2015
DOI: 10.1002/tal.1264
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced concrete roof exterior wide and conventional beam-column joints under lateral load

Abstract: SUMMARYPerformance of beam-column joints at roof level is one of the areas needing research in ACI 352R-02. Thus, behavior of roof exterior beam-column joints was evaluated by testing two half-scale roof wide and conventional beam-column joints effectively confined on three vertical faces under lateral quasistatic cyclic loading. Both of the specimens had conventional transverse beams. They were designed in accordance with ACI 318-11 and ACI 352R-02 provisions. It became clear by the tests that roof exterior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several methods for retrofitting beam‐column connections have been proposed in the past, but less attention has been focused on noninvasive strategy for seismic retrofit of deficient beam‐column connections . Jacketing with concrete is one of the earliest techniques to be introduced and is the most common solution for local rehabilitation of nonseismically detailed beam‐column joints, with several research projects that investigated the viability of this technique having been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for retrofitting beam‐column connections have been proposed in the past, but less attention has been focused on noninvasive strategy for seismic retrofit of deficient beam‐column connections . Jacketing with concrete is one of the earliest techniques to be introduced and is the most common solution for local rehabilitation of nonseismically detailed beam‐column joints, with several research projects that investigated the viability of this technique having been reported .…”
Section: Introductionmentioning
confidence: 99%